Using surfacing welding technology to manufacture economical molds - Mu, Yongcheng (Frontiers in Mechanical Engineering, 2024)
As an economical and fast process method for surface modification of materials, overlay welding is increasingly widely used in the manufacturing and repair of parts in various industrial sectors. This study combines grating projection measurement to design an economical mold arc additive process, and introduces point cloud simplification algorithm for wear and repair design of the mold structure. Then, a new method for manufacturing low-cost, long-life, and economical hot stamping die inserts is designed, using low-cost forged steel and cast steel as substrates and surface welding of high-temperature alloy wear-resistant layers. The experiment shows that the proposed algorithm for simplifying scattered molds has a good evaluation effect, without any gaps, and has a good retention effect on point clouds. The maximum and minimum distances are 0.45 mm and 0.025 mm, respectively. At temperatures of 200 and 300℃, the friction coefficient of cobalt based alloys is lower at 300℃ than at 200℃, and the fluctuation period is significantly longer than that at 300℃. The wear resistance of HSTS steel is the most stable, but the performance of cobalt based alloys is significantly higher than other alloys, indicating that cobalt based alloys have better performance. The compressive yield strength of iron-based alloys is the highest, and the hardness of iron-based alloys is the highest, at 53.2HRC. Therefore, iron-based alloys were selected as the surface wear-resistant layer welding material for economical molds with cooling channels, and cobalt-based alloys were also selected as the surface wear-resistant layer welding material for variable strength economical molds. The research results provide a reference for economic mold manufacturing and repair.